PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM PEMBUATAN DESAIN PROPERTI FILM - Owie, Anggra Agastyassa; Wibowo, Edy (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
Artificial Intelligence or AI is one of the technologies that is currently popular. Artificial Intelligence or AI is a computer system that is able to carry out tasks that usually require human intelligence. Film is a combination of efforts to convey messages through moving images. The demand for a picture of the setting and film properties sometimes requires a relatively short time to shorten the time in making a film. This study aims to explore the role of artificial intelligence (AI) in the creation and protection of film properties to improve copyright security. AI has the potential to offer innovative and creative solutions to the film property production process. This research method includes a literature review on the implementation of AI technology, case study analysis, and interviews with experts in the field of film. The results of this study show an analysis of artificial intelligence or AI technology that helps filmmakers create graphic properties using deepfake technology, prototypes for creating location setting simulations, 3D Prototyping, creating visual effects, arranging property logistics, AI for Virtual World Design and Augmented Reality (VR / AR) VR or AR technology allows AI to create interactive properties that adapt to the virtual environment in real-time